The importance of renosterveld conservation based on insect diversity sampled in West Coast Renosterveld in the Western Cape of South Africa - Stander, Arne (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScAgric)--Stellenbosch University, 2016.